Los ambientes estimuladores que garanticen el aprendizaje de los niños de 3 a 5 años de la Unidad Educativa “Luis Ulpiano de la Torre” del Cantón La Maná durante el periodo 2022-2023. - Chasig Tipanquiza, Melida Yolanda (2023)
The work carried out is based on stimulating environments that guarantee the learning of children from 3 to 5 years of age, where its general objective is to design didactic workshops on the use of stimulating environments as a methodological strategy that allows guaranteeing learning, where the Beneficiaries will be children from 3 to 5 years old in the Luis Ulpiano de la Torre Educational Unit. The focus of this research project had a qualitative approach with a projective research type and with a feasible and applied project modality; The techniques used were an interview with the authorities, teachers and a checklist applied to the students. According to the interviews it was possible to observe that the teachers have a low knowledge of how to work in the environments, with the collected data an analysis and interpretation of the information was carried out from a perspective of context and objectively.